A modified linear programming model for cost minimisation of Pangasius hypophthalmus feed formulation / Zuraida Alwadood, Anis Syahirah Rosli and Norlenda Mohd Noor - Alwadood, Zuraida; Rosli, Anis Syahirah; Mohd Noor, Norlenda (Universiti Teknologi MARA, Pulau Pinang, 2022)
Pangasius hypophthalmus or P.hypophthalmus is a common freshwater species cultured in Malaysia. Problems arise among farmers as the commercial pellets or feeds are too expensive. There is a limitation on the affordability of the farmers on the existing feed formulation due to its high and rising prices. In addition, there is no specific commercial pellet that is specifically designed to fulfil the nutrient requirement of P.hypophthalmus. Hence, this study is aimed to modify a linear programming model and propose the most optimum amount of nutrients in P.hypophthalmus feed formulation at each life cycle at minimum production cost, based on the solution of the modified model. The data on the nutrient requirement and ingredient composition for every life stage of P.hypophthalmus were gathered through literature and websites. The main ingredients used in the fish feed formulation are shrimp head flour, soybean meal, fish meal, cinnamon leaf powder, brewers’ spent grain, wheat pollard, rice bran and wheat flour. The novelties of the modified linear programming model are the inclusion of all four life stages of P.hypophthalmus in a single model, and the addition of a new supplement ingredient that is able to enhance the growth of P.hypophthalmus. The optimal solution revealed that the minimum production costs per 150 kg of feed mix for all four life stages are RM228.80, RM379.90, RM231.80 and RM233.10, respectively. The total price for the feed formulation is reduced by 26% to 37% as compared to the commercial feed price.